KEPUTUSAN PEMBELIAN BERDASARKAN PERSEPSI, MOTIVASI, DAN SIKAP PADA MARKETPLACE - Pelade Viora; AMA Suyanto (Faculty of Economic and Business, University of Pasundan, 2020)
The growth of e-commerce in Indonesia raises competition so companies must maintain the existence from total of 49 e-commerce in Indonesia by understanding consumer psychology, namely perception, motivation, and attitude that drive purchasing decision. The purpose of the study to determine consumer response and the influence of perception, motivation, and attitude of consumer toward purchasing decision on marketplace in Indonesia partially or simultaneously. The research method is quantitative with multiple linear regression analysis techniques. The results showed consumer responses to 80.5% perception, 82% motivation, and 81.4% attitude. And there are positive and significant influence partially or simultaneously from the perception, motivation, and attitude towards purchasing decisions on marketplace in Indonesia. Hope this research can be used as a reference for future researchers, specifically using different analytical techniques and business actors in the marketplace to improve services and respond to complaints.